THE ROLE OF GOVERNMENT EXTERNAL DEBT IN THE FORMATION OF THE FEDERAL BUDGET - D. Karandin; O. Revzon (Вестник университета)
The article considers the role of the public external debt of the budget of the Russian Federation. Also attention is paid to the influence of the level of public debt on the financial position of the country. Substantiated proposals to increase the external public debt management in the Russian Federation, resulting in proposed variant of increase of efficiency of public debt management Russia, optimization of the structure and minimize the consequences of its growth.